Antioxidant Protection against Curative and Palliative Doses of Ionizing Irradiation in Human Blood Decreases with Aging - Jelena Kasapović; Vesna Stojiljković; Ljubica Gavrilović; Nataša Popović; Zorka Milićević (The Scientific World Journal)
Reactive oxygen species (ROS) are independently recognized to play a significant role in radiation-induced damage on healthy tissue and in aging process. However, an age-related alteration of antioxidant (AO) system in radiation response in humans is poorly investigated. The aim of this paper was to evaluate the irradiation effects on the activities and expression of AO system in the blood of healthy women during aging. Blood samples were irradiated with curative and palliative doses of 2 Gy or 9 Gy γ-rays. AO capacity for detoxification of O2•− and H2O2 in response to 2 Gy γ-irradiation decreases in women above 58 years, while in response to 9 Gy shows signs of weakening after 45 years of age. Due to reduction of AO capacity during aging, cytotoxic effects of curative and palliative doses of irradiation, mediated by ROS, may significantly increase in older subjects, while removal of H2O2 excess could reduce them.